Minuman Kopi (Coffea)Terhadap Kekuatan Otot dan Ketahanan Otot Atlet Sepak Bola Usia Remaja di SSB PERSISAC - Sauma Rischi Nandatama; Ali Rosidi; Yuliana Noor Setiawati Ulvie (Jurnal Gizi, 2017)
In sports, coffee began to be consumed often before exercise to improve the performance of exercise and inhibits the occurrence of fatigue.  This study aims to prove the benefits of coffee on muscle strength and muscle endurance at the adolescent football athletes in the Football School PERSISAC of  Semarang City. This study is experimental study with randomized posttest control group design approach.The Total sample of 24 respondents were divided into two groups. Each group consisted of 12 respondents. The first group is the treatment group and the second group is the control group. The treatment group is given by cofee drink with the concentration 2 gr/150 ml. The sample is taken by using the random sampling methode. Data test muscle strength and muscle endurance tests obtained by measuring the push-ups and sit-ups in one minute, after the exercise was finished. The statistical test used was the Independent Samples T test. There are a differences results of tests of muscle strength and muscle endurance between the treatment group and control group. There are the effectsignificantly of giving coffee on muscle strength and muscle endurance.  There are a difference significantly of muscle strength between the treatment groups and the control group (p= 0.00). There are a difference significantly of muscle endurance between the treatment groups and the control group (p= 0.01). There is the effect of coffee on muscle strength and muscle endurance in adolescencesoccer athletes. It is advisable to consume coffee by the dose of 2 g / 150 ml immediately before exercise to review increasing muscle strength and muscle endurance athlete football.Keywords: Coffee, Muscle strength, Muscle endurance, Athletes, Footbal.